Mini-Company Information System - ARFINA AFWANI (NIM 13101028), MUHAMMAD
Large companies or organizations that have a lot of resources and complicated information stream having problem to control these resources and information. Type of organization that use hierarchies to conduct the command line where the leaders make every decision not evectively correct this problem. Mini-company concept gives a solution by distributing resposibilities to each people in the organization. This concept built autonomous units that can solve their problems and control their resources and information stream. This work present how to apply computer base informations system in mini-company concept. First, it's explain the mini-company concept and modelling the required system. Than the model is implemented by creating web base information system. The presented example in this work can clarify how to implement mini-company concept using this information system.